VD_FINDINFO HC / 2010 / 209 vom 9. März 2010 - VD Tribunal cantonal (2010)
ACTION EN MODIFICATION, JUGEMENT DE DIVORCE, OBLIGATION D'ENTRETIEN, CONJOINT, ACTION EN RÉDUCTION | 129 al. 1 CC, 138 al. 1 CC, 451 ch. 3 CPC, 452 al. 2 CPC